PIJAT BAYI OLEH PEMIJAT BAYI TRADISIONAL DI KECAMATAN MEDAN AREA TAHUN 2014 - adelia bastian; Syarifah, MS; Tukiman, MKM (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACTIt should be admitted that the medical technology that exists today is not fully able to overcome any health problems, especially with the more great variety of diseases and the factors that caused, not to mention the diseases would be known as the impact of progress in the field of detection of the disease, such as genetic diseases, malignancies, etc. . With this awareness inevitably medical world can not turn a blind eye to the progress of science and technology of treatment without medicine, although sometimes there is a method that looks irrational including baby massage (Lopez, 1995).